Leukocyte telomere length associated with glioma risk and survival. Issue 1 (18th October 2020) - Shen, Jie; Song, Renduo; Ye, Yuanqing; Gong, Ye; Zhao, Hua
Abstract: Background: Relative telomere length (RTL) in leukocytes has been linked to risks of many cancers, although how leukocyte RTL contributes to adult glioma has rarely been studied Aim: We performed a case‐control study to evaluate the association between RTL in leukocytes and glioma risk in 565 glioma patients and 1130 healthy controls Methods and results: Overall, mean leukocyte RTL was significantly higher in cases than controls ( P  < .001). Longer RTL was associated with a 1.32‐fold increased risk of glioma (odds ratio [OR] = 1.32, 95% confidence internal [CI] = 1.13‐1.64). In quartile analysis, a significant dose‐response relationship was noted ( P  < .001). Compared to the first quartile with shortest RTL, the fourth quartile with longest RTL was associated with 1.51‐fold elevated risk of glioma (OR = 1.51, 95% CI = 1.10‐2.18). In further stratified analysis by clinical characteristics at baseline, the significant relationship was observed among cases with aggressive tumor characteristics, including glioblastoma multiforme (GBM), high tumor grade, and absence of IDH mutation and 1p/19q co‐deletion. Finally, we evaluated leukocyte RTL in GBM prognosis. We found that longer RTL was associated with increased probability of overall survival (hazard ratio [HR] = 0.88, 95% CI = 0.70‐0.98), and progression/recurrence‐free survival (HR = 0.81, 95% CI = 0.60‐0.93) in patients with primary GBM Conclusion: Our findings indicate that longer RTL is significantly associated with glioma risk, and the association differs by tumor aggressiveness. Also, RTL in leukocyte could be a prognostic predictor of survival and progression in patients with GBM.